Christian missions and the judgement of God - Paton, David Macdonald, 1913-1992; Paton, David M.M. (Grand Rapids, MI Eerdmans, 1996)
Includes bibliographical references.
Keywords: Paton, David Macdonald, -- 1913-1992; Missions -- philosophy